Pengaruh Persepsi Risiko dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Secara online Saat Terjadi Pandemi Covid 19 di Seberang Ulu II Kota Palembang - Muhammad Rudi Rahman Wijaya; Sri Rahayu; Nadia Afriliana Nadia Afriliana (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The formulation of the problem in this study is, is there an effect of risk perception and consumer trust on online purchasing decisions during the Covid-19 pandemic in Seberang Ulu II, Palembang City. This study aims to determine the effect of risk perception and consumer confidence on online purchasing decisions during the Covid-19 pandemic in Seberang Ulu II, Palembang City. The research was conducted using associative research methods. The population in this study were residents in the Seberang Ulu II District of Palembang City. The sampling technique used purposive sampling method with a sample size of 100 people. The data used are primary data. Data collection method through questionnaire. The data analysis used is qualitative and quantitative analysis. The analysis technique used is multiple linear regression analysis, F test, t test and coefficient of determination (R2) with a significant level of 5%. The results showed that there was an effect of risk perception and consumer trust on online purchasing decisions during the Covid-19 pandemic in Seberang Ulu II, Palembang City. This is evidenced by the results of multiple linear regression Y = 1.457 + 0.294X1 + 0.289X2. The results of the F test show that there is a positive and significant influence on risk perceptions and consumer trust on purchasing decisions with the value of Fcount (33.127)> F table (3.09) with a significant 0.000 <sig α = 0.05. The t-test results revealed that the perception of risk had a significant influence on purchasing decisions with a tcount (3.221)> ttable (1.66) with a significance of 0.002 <sig α = 0.05. Consumer trust has an effect on purchasing decisions with tcount (3,415)> t table (1.66) with a significance of 0.001 <sig α = 0.05. The determination coefficient test of 0.394 (39.4%) variables of risk perception and consumer confidence is able to explain online purchasing decisions during the Covid-19 pandemic in Seberang Ulu II, Palembang City. Meanwhile, 60.6% is explained by other factors outside the research.